The myth of development : non-viable economies and the crisis of civilization - Rivero B., Oswaldo de (Global issues series (New York, N.Y. : 1999), 2010)
The message of this courageous classic book is that the benefits of development, so long promised over the past sixty years, have not come about for most people. Nor are they going to. State-driven and market-led development models have both failed. Oswaldo de Rivero argues that the 'wealth of nations' agenda must be replaced by a 'survival of nations' agenda. This much-anticipated new edition features both updated statistics and fresh material, including an essential new argument that the present global crisis is not simply economic but a much more profound crisis of 'the California Model': a.